VISION OF INTEGRATIVE APPROACH TO TEACHING STUDENTS OF PHILOLOGY IN HIGHER TECHNICAL EDUCATIONAL INSTITUTIONS - Рудіна, М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
Vision of integrative approach in higher education as the methodological basis of teaching students at universities has been carried out. It was highlighted that to learn foreign languages technical higher institutions are chosen by applicants. Based on domestic and foreign science’s investigations educational perspective to integrative approach in education has been described. It was summarized that integrative approach fixed in time and place in the context of scientific redefinition and revival of theoretical multiplicity of pedagogy assimilates traditional content of modern education, provides the quality of modernized education. It has been highlighted that integrative approach is the basis of the unity of sectoral knowledge and foreign language competence as the asset of student’s knowledge. It is emphasized that integrative approach is the conceptual element of universal theoretical model of higher education that regulate: educational curricula within the specialty; integrative training courses; textbooks and training manuals in translation. All these factors further to get transferable abilities. It has been proved that there is a great number of components integrate in teaching students of philology: great deal of content (foreign language, sectoral vocabulary, translation, methods of teaching English in higher and secondary education, psychological and pedagogical knowledge); innovative methods and techniques of providing foreign and translation competence; informative content; legal and legislative support etc. These components denote the perspectives of integrative approach as an object of scientific investigation. It has been investigated that young people, choosing philological education in higher technical educational institutions, evaluate advantages of transferable abilities, which strengthen the competitiveness of professional, expand the sphere of demand for the professional, assist to fulfil the ambitions